2007
DOI: 10.1016/j.micres.2006.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Production of tannase from Aspergillus ruber under solid-state fermentation using jamun (Syzygium cumini) leaves

Abstract: Tannase producing fungal strains were isolated from different locations including garbages, forests and orchards, etc. The strain giving maximum enzyme yield was identified to be Aspergillus ruber. Enzyme production was studied under solid state fermentation using different tannin rich substrates like ber leaves (Zyzyphus mauritiana), jamun leaves (Syzygium cumini), amla leaves (Phyllanthus emblica) and jawar leaves (Sorghum vulgaris). Jamun leaves were found to be the best substrate for enzyme production unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 13 publications
8
51
2
1
Order By: Relevance
“…Lekha and Lonsane [10] also reported that tannases are acidic proteins with an optimum pH 5.5. Rakeshkumar et al [17] reported an optimum pH of 5.5 for tannase production by Aspergillus ruber, Aspergillus awamori [18] which is in good agreement with the current results Obtained …”
Section: Effect Of Ph On Production Of Tannasesupporting
confidence: 91%
“…Lekha and Lonsane [10] also reported that tannases are acidic proteins with an optimum pH 5.5. Rakeshkumar et al [17] reported an optimum pH of 5.5 for tannase production by Aspergillus ruber, Aspergillus awamori [18] which is in good agreement with the current results Obtained …”
Section: Effect Of Ph On Production Of Tannasesupporting
confidence: 91%
“…The production of the enzyme was done in 250-mL Erlenmeyer fl asks containing 50 mL of fermentation medium based on Czapeck-Dox broth containing (in g/L): NaNO 3 30. A er cooling the fl ask to room temperature, tannic acid (2 %, by mass per volume) was added a er sterilisation through a 0.22-µm membrane fi lter, the content was inoculated with three mycelial disks of P. guepinii (1.3 cm) and then incubated at 30 °C, under shaking (150×g) for 48 h.…”
Section: Submerged Fermentationmentioning
confidence: 99%
“…Native to India, Ceylon, Malaysia and Australia (1), it has been widely grown as an ornamental plant, mainly along the coast, and it can be found in several Brazilian states such as Minas Gerais, Rio de Janeiro and São Paulo (2). Several studies have determined the presence of hydrolysable tannins in the plant, particularly in the seeds, increasing the chance of obtaining endophytic microorganisms that (3)(4)(5). Tannins can also be found in the sap, fruits, leaves, skin and root system (6).…”
Section: Introductionmentioning
confidence: 99%
“…The biodegradation is due to their capacity to excrete various extracellular enzymes [13,14]. The efficiency of the biological treatment can be enhanced by carefully selecting the operational conditions that have been observed to influence the decolorization and enzymes' production [7,15,16].…”
Section: Introductionmentioning
confidence: 99%